2020
DOI: 10.1111/hex.13161
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a physician’s recommendation and gender on informed decision making: A randomized controlled study in a simulated decision situation

Abstract: Objective This study examined the influence of physicians’ recommendations and gender on the decision‐making process in a preference‐sensitive situation. Methods N = 201 participants were put in a hypothetical scenario in which they suffered from a rupture of the anterior cruciate ligament (ACL). They received general information on two equally successful treatment options for this injury (surgery vs physiotherapy) and answered questions regarding their treatment preference, certainty and satisfaction regardin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Future studies could investigate if there is an interaction effect of gender and communicative behavior of physicians on patients’ perceived opportunity for SDM. Perhaps the communication style of physicians has a stronger impact than gender itself [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Future studies could investigate if there is an interaction effect of gender and communicative behavior of physicians on patients’ perceived opportunity for SDM. Perhaps the communication style of physicians has a stronger impact than gender itself [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the appropriate use of particular communication styles depends on the specific patient groups and the consultation goals. In addition, it has been shown that patients tend to follow the physician's advice and decide against their own initial treatment preferences [7][8][9]. In situations where patient preferences are of great importance, recommendations should be used carefully [10].…”
Section: Physician-patient Communicationmentioning
confidence: 99%
“…In situations where patient preferences are of great importance, recommendations should be used carefully [ 10 ]. If the original preference is already in line with the physician’s recommendation, the patient’s decision-making certainty and satisfaction increases [ 9 ]. Good communication gives physicians the opportunity to pass on their knowledge about a specific disease as well as diagnostic and therapeutic considerations to their patients; it is essential for this information to be understood correctly by the patient.…”
Section: Introductionmentioning
confidence: 99%